Erythrocyte glycocalyx sensitivity to sodium is associated with salt sensitivity of blood pressure in women but not men - Masenga, Sepiso K.; Hamooya, Benson M.; Patel, Kaushik P.; Kirabo, Annet (Frontiers in Nutrition, 2024)
Background While salt sensitivity of blood pressure (SSBP) is a risk factor for hypertension, end-organ damage and death, most studies are conducted in western countries and in White people. We previously found that the prevalence of SSBP in Blacks living in Sub-Saharan Africa is as high as 75–80% like what has been reported in the west. Erythrocyte glycocalyx sensitivity to sodium (eGCSS), a marker of sodium-induced damage to the erythrocyte and vascular endothelial glycocalyx is thought to be related to blood pressure perturbations associated with salt intake. We hypothesized that SSBP correlates with eGCSS differently in men and women in Black people. Methods We conducted a cross sectional study using data from our recent clinical trial from Livingstone University Teaching Hospital among 117 normotensive young adults. We used a “salt blood test” to determine eGCSS and an immediate pressor response to oral salt (IPROS) for the diagnosis of SSBP. Results The proportion of males were equal to females and the median age (interquartile range) of the participants was 29 (22–45) years. The eGCSS scores were higher in salt-resistant females compared to salt-sensitive females and males. eGCSS correlated negatively with SSBP (AOR 0.98, 95% CI 0.97–0.99, p = 0.008), however, this relationship was driven by female sex and abrogated by male sex. Although blood pressure elevations exhibited a sustained bimodal pattern in both sexes, in males, systolic and diastolic blood pressure never returned to baseline during the time course as it did in females. Conclusion In this study, eGCSS correlated negatively with SSBP in black women but not in black men and the pressor response to dietary salt was significantly higher in men compared to women. These results suggest that women tend to have a higher disruption of the vascular endothelial glycocalyx by an acute salt load, implying that acute changes in blood pressure may not be driven directly by the endothelial glycocalyx. Our findings suggest a novel mechanism linking eGCSS and SSBP with potential implications for sex differences in salt-induced cardiovascular disease. Clinical trial registration: https://clinicaltrials.gov/, identifier [NCT04844255].